Tradition and Transition in Nigeria: Historical evolution and Contemporary Challenges of the Chieftaincy Institution - OYEDOKUN, Mojeed Oyetunji; AKANBI, Shola Ahmed; MALANG, Fanneh (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This paper examines tradition and transition in Nigeria with emphasis on historical evolution and contemporary challenges of the chieftaincy institution. Utilising historical documents, anthropological research, and current policy discussions, the study investigates how the colonial policy of indirect rule reshaped indigenous leadership systems and incorporated them into the framework of state governance. Despite the growing pressures of democratisation, urbanisation, and legal reforms, the chieftaincy institution has endured in the post-independence age as a site of cultural validity, political power, and communal identity. The politicisation and commercialisation of chieftaincy titles, as well as conflicts between traditional authority and constitutional frameworks, are highlighted in the paper. The paper contributes to the body of knowledge on the role of traditional institutions in post-colonial African states by situating the chieftaincy system within larger narratives of continuity and change. The paper concludes that any sustainable integration of traditional institutions into modern governance must address issues of accountability, equity, and cultural representation.